Advancing methodologies of conducting literature review in management domain - Rana, Sudhir; Singh, Sakshi; Singh, Jagroop (Review of management literature ;, 2023)
Giving new insight into the theories behind management literature reviews, Advancing Methodologies of Conducting Literature Review in Management Domain explores a range of novel ideas on how to plan, organize, synthesize, and present the results from previous literature from across management research. Specific areas examined in this volume include planning and setting the objectivity of review papers, search processes, data selection and screening, review types and designs, and evaluation criteria, validity, and reliability.